PERBANDINGAN EFEK TERAPI TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAN INFRA RED (IR) DENGAN INFRA RED (IR) DALAM PENGURANGAN NYERI PADA PENDERITA ISCHIALGIA DI RSUD DR. M. HAULUSSY AMBON - Isabella Jeklin Barolla; Maureen J. Paliyama; Laura B.S. Huwae (Fakultas Kedokteran Universitas Pattimura, 2021)
Ischialgia is a condition of pain, weakness, burning, and tingling along the back of the leg caused by inflammation which causes irritation of the ischial nerve and direct compression on the nerve, causing motor dysfunction which is also often exacerbated by flexion of the spine, twist and bend to the side. Based on data from the WHO global health estimates technical paper, it shows that the prevalence rate of ischialgia is high enough for the overall presentation of disease presented. Globally, the prevalence of ischialgia at all ages reaches 8.2% and is the main cause of years lived with disability (YLD). Based on this, this study aims to compare the effects of transcutaneous electrical nerve stimulation (TENS) and infrared (IR) therapy in reducing pain in patients with ischialgia at RSUD dr. M. Haulussy Ambon 2020. This research is analytical based on secondary data taken from the patient’s medical records. The number of samples in this study were 80 patients who were taken using purposive sampling method. The results of this study showed that the use of IR therapy and combination therapy of TENS and IR is considered effective with a mean VAS value at the ti me of pre-test -(before therapy) of around 5.74± 0.83 (95% CI; 2.39 - 2.76) and the mean value on the post-test was 3.17±0.95 (95% CI; 2.39-2.76);The use of IR therapy was considered ineffective with a mean VAS value at the time of pre-test (before therapy) of about 5.75±0.74 (95% CI; 1.91-2.28) and a mean value on the post-test of 3.65±0.92 (95% CI; 1.91-2.28); and the use of TENS and IR combination therapy is considered effective with a mean VAS at pre-test (before therapy) of about 5.74±0.92 (95% CI; 2.84-3.31) and a mean value on the post-test of about 2,66 ± 0.67 (95% CI; 2.84-3.31).